Foods That Improving the Immune System against Covid-19 and Its Infectiousness - Eyyüp Karaogul; İbrahim Hayoğlu; Akif Cicek; Mustafa Beğenç Taşcanov; Zülkif Tanrıverdi; Sümeyra Cicek; Berika Hayoğlu (Zenodo, 2021)
Abstract Background: The main aim of this study is to interpret nutrients that can potentially increase immunity to coronavirus (COVID-19) and reduce the risk of getting sick. Methods: Severe acute respiratory syndrome about coronavirus [SARS-CoV] and SARSCoV-2 as known pathogenic coronaviruses for Human enter to their target cells through angiotensin-converting enzyme 2 (ACE2), which is stated by epithelial cells of the lung, intestine, kidney, and blood vessels (Fang et al., 2020, Wan et al., 2020). Moreover, cohort of patients with COVID‐19 were decreased Protein C level after infection to cell (Panigada et al.). These situations could be caused cross-linked fibrin clot. In this case, inhibition of ACE2 and higher immunity of protein C could be possible reduced the risk of COVID-19. The levels of ACE2 and Protein C are potentially important. If the levels of ACE2 and Protein C could be controlled any nutrients, the risk could be potentially prevented. So, effects of ACE2 and Protein C were evaluated from literature. Results: The level of angiotensin-converting enzyme 2 is great potential to avoid coronavirus disease (COVID-19). In this case, the nutrition foods supplied inhibition of ACE2 were evaluated in this study. In Table 1, it is showed list of the nutrition food as caused inhibition of angiotensin-converting enzyme 2 (ACE2 Conclusion: The nutrients that can potentially increase immunity to coronavirus (COVID-19) and reduce the risk of getting sick has great important in this time. It is also important to slow down the factors that cause it. The levels of ACE2 and Protein C are potentially important. If the levels of ACE2 and Protein C could be controlled any nutrients, the risk could be potentially prevented. It was noticed that the immunity against COVID-19 could be improved with Cuttlefish, Sardinelle (Sardinella aurita), Rohu (Labeo rohita), Grass carp, European Carp (Cyprinus carpio L.), Cirrhinus mrigala, Salmon (Salmo salar), Katsuo-bushi, Acetes indicus, Common Oat (Avena sativa), Goat milk ...